2016
DOI: 10.2147/copd.s109016
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of activation for self-management in patients with COPD

Abstract: BackgroundCOPD self-management is a complex behavior influenced by many factors. Despite scientific evidence that better disease outcomes can be achieved by enhancing self-management, many COPD patients do not respond to self-management interventions. To move toward more effective self-management interventions, knowledge of characteristics associated with activation for self-management is needed. The purpose of this study was to identify key patient and disease characteristics of activation for self-management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
47
3
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 44 publications
14
47
3
5
Order By: Relevance
“…Previous studies have also observed differences between patients who pro-actively monitored the course of an exacerbation and contacted their HCP on time and patients who postponed health care contact until feeling an urgency for medical care 21,24,30,41. Finally, regarding smoking in relation to self-management, our study concurred with earlier studies in showing that smoking was not an explanatory factor for self-management behavior 42,43…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have also observed differences between patients who pro-actively monitored the course of an exacerbation and contacted their HCP on time and patients who postponed health care contact until feeling an urgency for medical care 21,24,30,41. Finally, regarding smoking in relation to self-management, our study concurred with earlier studies in showing that smoking was not an explanatory factor for self-management behavior 42,43…”
Section: Discussionsupporting
confidence: 88%
“…These results correspond to those of a study by Bos-Touwen et al, which identified physical health status and social support as associated with activation for self-management in a population living with chronic diseases (COPD, type 2 diabetes mellitus, chronic heart failure, and chronic renal disease) 18. However, in a later study of determinants of self-management in COPD patients only, illness perception and GOLD stage, but not social support, were identified as explanatory determinants 54. This difference in results illustrates the complexity of self-management of COPD.…”
Section: Discussionsupporting
confidence: 80%
“…Our qualitative feedback from our intervention teams highlighted the presence of multiple inhalers, often containing overlapping formulations in the homes of study subjects and an associated poor level of inhaler technique. COPD patients do not easily engage in self-management programs due to many factors,50 and because of these challenges, intensive longer follow-up than in our study is required. In addition, given the known cognitive impairment and reduced levels of health literacy in this patient population,51,52 it is not hard to imagine that an intensive and sustained humanomics-based intervention would be effective 53…”
Section: Limitations and Reasons For Efficacymentioning
confidence: 90%